Smallholder access to biotechnology: case of Rhizobium inocula in Kenya - Odame, Hannington (2002)
Using the case study of Rhizobium inocula project in Kenya, this paper argues that the main challenge to enhancing smallholder access to biotechnology lies in addressing the sources of institutional constraints in agricultural innovation processes. These constraints include sunk costs, uncertainty and political influence. How are mechanisms such as reducing uncertainty, building trust, and creating incentives at both national and local levels likely to improve smallholder access to Rhizobium inocula and transgenic crops in Kenya? - Reproduced.
Keywords: Biotechnology; Agricultural biotechnology